A Conceptual Framework for Intellectual Capital to Drive Digital Transformation in Indonesia's Transportation Sector - Fariz, Fariz; Winarsih, Tutik (APMBA (Asia Pacific Management and Business Application), 2025)
The transportation sector faced substantial challenges during the COVID-19 pandemic, primarily due to a lack of robust digital infrastructure and reliance on unreliable data. This study aims to tackle these issues by implementing a digital transformation strategy focused on reengineering business processes and introducing an innovative intellectual capital model specifically designed for Indonesia's government transportation sector. This research marks a pioneering effort in developing unique measurement indicators and dimensions for this intellectual capital model. The model's creation was informed by an extensive literature review, which led to a survey distributed to 302 field experts. The proposed framework includes informational, human, structural, and relational capital, constructed through structural equation modeling (SEM) and analyzed with AMOS software. Informational capital is defined as the combined assets that generate value, encompassing data, information, knowledge, technology, and tools. Statistical analysis showed a moderate level of intellectual capital readiness among surveyed organizations. 'Knowledge Management' displayed the highest readiness level, followed by 'Planning and Processes.' Conversely, 'Transformational Technologies' and 'Creativity and Innovation' scored lowest in readiness. These results suggest that organizations in this sector require a broad set of skills and competencies to boost creativity and innovation while effectively utilizing digital technologies to enhance intellectual capital. To successfully implement a digital strategy, organizations must develop essential competencies, emphasize the importance of informational assets, and cultivate a culture supportive of change